A meta-analysis on the relationship between the use of electronic media and psychological well-being - Dong Liu; Roy F Baumeister; Chia-Chen Yang (Elsevier, 2024)
The effect of digital media use on psychological well-being has been debated among scholars and the public for a long time. This study investigates the relationship between various types of media use and psychological well-being. It was proposed that communication media such as phone calls, texting, and instant messaging positively correlate with well-being. In contrast, the usage of social network sites (SNSs) and online gaming would be negatively correlated. To test this hypothesis, we conducted a meta-analysis of 292 studies. The meta-analysis revealed a positive correlation between phone calls and psychological well-being and a negative correlation between online gaming and psychological well-being. However, the overall correlations between digital media use and well-being were weak. Furthermore, the impact of digital media on well-being was influenced by how technology was utilized. For example, using SNSs for entertainment was linked to better well-being, whereas self-presentation and content consumption on SNSs were correlated to poorer well-being.